Pengaruh Lingkungan Sekolah terhadap Konsep Diri Sosial Murid di SD Katolik V ST. Agustinus Tomohon - Marianus Muharli Mua; Secondary Putri Nahumuri (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aimed to examine the condition of the school environment, determine the level of students' social self-concept, and analyze the influence of the school environment on students' social self-concept at St. Agustinus V Catholic Elementary School, Tomohon. This study employed a quantitative approach using an ex post facto correlational research design. The sample consisted of 77 students selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire. The data were analyzed using descriptive statistics, prerequisite tests, simple linear regression, the t-test, and the coefficient of determination. The findings revealed that the school environment was categorized as moderate, with a mean score of 53.01, while the students' social self-concept was also categorized as moderate, with a mean score of 49.42. The results of the simple linear regression analysis produced the equation Y = 3.143 + 0.873X, indicating that the school environment had a positive effect on students' social self-concept. Furthermore, the t-test yielded a significance value of 0.000 (< 0.05), indicating a positive and statistically significant effect of the school environment on students' social self-concept. The coefficient of determination (R²) was 0.451, indicating that the school environment accounted for 45.1% of the variance in students' social self-concept, while the remaining 54.9% was explained by other factors not examined in this study.